Pengaruh Kualitas Produk, Kualitas Layanan, Harga dan Tempat terhadap Keputusan Pembelian Pada Resto and Cafe Bukit Pamona - Nadia Claudia; Mikhael Jibrael Balo; Charis Elfis Fajar Sangkide; Sany Feria Juliana (Universitas 45 Surabaya, 2025)
Competition in the culinary industry after the pandemic is getting stronger, so business actors need to understand how consumers make purchasing decisions. Bukit Pamona Restaurant & Cafe in Tentena, Central Sulawesi, was chosen as a research context because it was able to survive and attract visitors in the midst of increasing competition. This study examines the influence of product quality, service quality, price, and location on purchasing decisions. The research uses a quantitative approach based on positivism. Samples were obtained through incidental sampling techniques on 50 customers. Data were collected using a Likert scale questionnaire, then processed by multiple linear regression using SPSS. Before the main test, the instrument is assessed through validity and reliability tests as well as verification of classical assumptions (normality, heteroscedasticity, and multicollinearity). The results showed that in the partial testing only the location variable had a significant effect, while the product quality, service quality, and price were insignificant. In contrast, in simultaneous testing, these four variables together had a significant effect on purchasing decisions. An Adjusted R² value of 0.425 indicates that the model explains 42.5% variation in purchasing decisions. Substantively, these findings highlight the role of strategic and natural locations as the main driver of consumer preference for Resto & Cafe Bukit Pamona.